Inflammation and outer blood-retina barrier (BRB) compromise following choroidal murine cytomegalovirus (MCMV) infections - Xu, Jinxian (Mol Vis, 2018)
PURPOSE: The purpose of this study was to determine whether the blood–retina barrier is compromised by choroidal murine cytomegalovirus (MCMV) infection, using electron microscopy. METHODS: BALB/c mice were immunosuppressed with methylprednisolone and monoclonal antibodies to CD4 and CD8. At several time points post-MCMV intraperitoneal inoculation, the eyes were removed and analyzed with western blotting and immunoelectron microscopy for the presence of MCMV early antigen (EA) and the host protein RIP3. Posterior eyecups from RIP3(−/−) and RIP3(+/+) mice were cultured and inoculated with MCMV. At days 4, 7, and 11 post-infection, cultures were collected and analyzed with plaque assay, immunohistochemical staining, and real-time PCR (RT–PCR). RESULTS: MCMV EA was observed in the nuclei of vascular endothelial cells and pericytes in the choriocapillaris. Disruption of Bruch’s membrane was observed, especially at sites adjacent to activated platelets, and a few RPE cells containing some enlarged vesicles were found directly beneath disrupted Bruch’s membrane. Some virus particles were also observed in the enlarged vesicles of RPE cells. Levels of the RIP3 protein, which was observed mainly in the RPE cells and the basement membrane of the choriocapillaris, were greatly increased following MCMV infection, while depletion of RIP3 resulted in greatly decreased inflammasome formation, as well as expression of downstream inflammation factors. CONCLUSIONS: The results suggest that systemic MCMV spreads to the choroid and replicates in vascular endothelia and pericytes of the choriocapillaris during immunosuppression. Choroidal MCMV infection is associated with in situ inflammation and subsequent disruption of Bruch’s membrane and the outer blood–retina barrier.